Estrutura e funcionamento da alça microbiana nos sedimentos da Baía do Araçá, São Sebastião - SP - Andrade, Vanessa da Costa [UNESP] (2015)
It is known that great part of the global primary occurs in the oceans, and a problem is to understand how the organisms use this carbon, what are the patterns of the spatial-temporal variations of carbon and of the energy flow. Thus, the interest in the carbon cycle is increasig in recent years due to the increase of global problems, such as climate change and the increase of population in coastal areas. The microbial loop leads energy and carbon, by bacteria, to the other trophic levels, and it also promotes the assimilation of inorganic elements biologically relevants, such as nitrogen and phosphorus, in organic matter in the water column, which are extremely biologically importants. This study aims to analyze the structure and the functioning of the microbial loop, quantifying its elements, check the densities variations and correlate with other analyzed factors, such as metal contaminants, organic matter and hydrocarbons. Sediment samples were collected at 37 points, divided into two regions (intertidal and subcoastal), during the period of one year. The samples were processed for granulometric analyzis, organic matter, total organic carbons, hydrocarbons, and microbiological components. It was observed that the highest densities of microrganisms were at the subcoastal region. There was a negative correlation between the densities of heterotrophic bacteria and nanoflagellates, which may indicate bacterivory. Variations of organic matter throughout the study directly affected the heterotrophic bacteria populations